DINAMIKA PENGUSAHA BATIK DI DESA SENDANG DUWUR PACIRAN LAMONGAN 1950-2012 - Ida Wahyuni (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2023)
Sendang Batik is a local household industry that is very profitable for the community. Because its appearance can boost the economy of the residents of Sendang Village. This article study aims to look at the dynamics of the batik industry in Sendang Duwur Village, in order to introduce local batik to the national and international level. In this research article, the author uses a descriptive qualitative approach because it is a field study. As for the research method, the author uses a historical method which has four stages in the study, namely, heuristics, criticism, interpretation, and historiography. In this research, the results can be found that the batik tradition began with Sunan Sendang Duwur's wife, namely, Dewi Tilarsih, who created this activity to fill her free time. The Batik industry starts from the homes of each community until the formation of batik industry communities. There is capital, labor, marketing, and the economy of the batik industry. The batik industry in Sendang Duwur Village is profitable for entrepreneurs in the economy. Because before the existence of the batik industry, people only worked as farmers whose economy could only be made for daily needs. With the emergence of the batik industry in Sendang Duwur Village, the people can live well enough to be able to send their children to college. There are various variants and motifs in Sendang Duwur Batik, namely leaves, flowers, whiteness, namkathil, singo kok, milkfish catfish. Apart from motifs or variants, Sendang Duwur batik also has various types of products, namely, Shawl, Jarik, Udeng, Sarong, Batik Shirt and Krudung. The many types of variants and motifs that Sendang Duwur batik has are encouraged by the community itself, as well as from the local government.